Design And Evaluation Of Medication Error Reporting Using Application (Mera) Among Healthcare Professionals In Perak: A Mixed-Method Approach - Visuvasam, Doris George (2020)
Medication error (ME) causes substantial monetary, clinical and emotional impact on patients. Reporting ME is the corner stone that promotes learning and safety improvements to prevent future MEs. However, in Malaysia underreporting of ME is high and skewed by pharmacists as reporters at hospitals settings. The aim of this research is to design and test a mobile phone application to complement existing reporting system. This research was conducted in three phases. First phase was conducted to determine acceptability and feasibility of mobile application to report ME using electronic questionnaire among doctors and pharmacists in Perak. Second phase of the study, was to design and test the developed application using mixed method analysis. Usability testing was used incorporating three methods: task performances, questionnaire and focus group discussions (FGD). Final phase was efficacy testing of application (MERA) was conducted in a single tertiary public-funded hospital using pre-post design to compare weekly report, reporting time, types of reports and reporters. In phase one, 84%, (283/334) of doctors and pharmacist in Perak used medical application for work and 79% (26/334) have fast to average internet connections at work. Majority, 87% (289/334), would report ME using an application if one was made available. In phase two, three usability testings involving 45 testers. Total 135 reports successfully reported with 79% of reports were correct. Median total SUS scored significantly increased in first session 67% to 88%, p<0.001 in third session.